The possible application of the Islamic principles of equity to Malaysian Land Law: a discussion - Mohamad, Nor Asiah (LexisNexis, 2008)
The application of equitable principles owns a respectable position in almost all legal subjects; land is not an exception. The presence of the prohibitive provision under s 6 of the Civil Law Act 1956 does not effect the original role person involved in land transactions. This feature of equity has become acceptable in all jurisdistions in the world. Nevertheless, as it will be shown in this articles, the yardstick used to measure equity may differ from one situation to another. This article holds that the concept of justice as promoted under the equitable principles of Islam may look similar to the English concept of equity, yet differs in its sources and objectives. In Islam, the knowledge of the objectives of Shariah determines the ability to exercise ijtihad (interpendent reasoning) and helps the judges arrive at a judgement that renders justice to both parties involved in the dispute. It is possible to invoke all concepts of equity, either from English or other laws, as long as they conform to the objectives of the Shariah.